An Illustrated History oh the USA - OCallaghan, Bryn. (Edinburgh Longman, 2001)
This is a companion volume to "An Illustrated History of Britain". It traces the history of the USA from the time of the Amerindians, through to the arrival of the Europeans, to the present day. Topics covered include colonial life, the Civil War and the American involvement in Vietnam. Each chapter consists of two or three double page spreads with inset material highlighting some of the characters or events mentioned in the main text.
Keywords: History